2019
DOI: 10.5312/wjo.v10.i12.424
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of a novel serum mRNA gene panel for diagnosis of acute septic arthritis

Abstract: BACKGROUNDSeptic arthritis is an orthopedic emergency requiring immediate surgical intervention. Current diagnostic standard of care is an invasive joint aspiration. Aspirations provide information about the inflammatory cells in the sample within a few hours, but there is often ambiguity about whether the source is infectious (e.g. bacterial) or non-infectious (e.g. gout). Cultures can take days to result, so decisions about surgery are often made with incomplete data. Novel diagnostics are thus needed. The “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Furthermore, the model could be potentially improved by addition of more sensitive biomarkers such as procalcitonin or novel RNA signatures. [28][29][30][31] In addition, repeated CRP measurement could aid in the differentiation of bacterial infections. 32 Ideally, predictors should be readily available at the point-of-care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the model could be potentially improved by addition of more sensitive biomarkers such as procalcitonin or novel RNA signatures. [28][29][30][31] In addition, repeated CRP measurement could aid in the differentiation of bacterial infections. 32 Ideally, predictors should be readily available at the point-of-care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical prediction rules should aim to influence clinical important decisions such as need for antibiotic treatment or hospital admission. Furthermore, the model could be potentially improved by addition of more sensitive biomarkers such as procalcitonin or novel RNA signatures 28–31 . In addition, repeated CRP measurement could aid in the differentiation of bacterial infections 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The biodegradable electrosprayed nano/microparticles released high concentrations of antibiotics into the synovial knee tissue of rabbits for more than 2 weeks which was well above the MIC 90 for S. aureus . • Schulz et al [ 185 ] reported the use of a novel diagnostic method termed the “Sepsis MetaScore” (SMS) which is an 11-mRNA host immune blood signature. This represents a rapid blood test that can distinguish between bacterial inflammation and non-infectious causes of inflammation thus directing correct treatment to be followed at the earliest.…”
Section: Methodsmentioning
confidence: 99%
“…• Schulz et al [ 185 ] reported the use of a novel diagnostic method termed the “Sepsis MetaScore” (SMS) which is an 11-mRNA host immune blood signature. This represents a rapid blood test that can distinguish between bacterial inflammation and non-infectious causes of inflammation thus directing correct treatment to be followed at the earliest.…”
Section: Methodsmentioning
confidence: 99%
“…This lack of biological and clinical heterogeneity, in turn, reduces the generalizability of findings. Using a multicohort analysis framework [17], we have repeatedly demonstrated that leveraging biologically, clinically, and technically heterogeneous cohorts identifies a more robust generalizable gene signature compared to using a single homogeneous cohort [18][19][20][21][22][23][24][25][26][27][28] and can be translated in a diagnostic test for use in clinics [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%